Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15282/ijame.14.2.2017.17.0346
|View full text |Cite
|
Sign up to set email alerts
|

The use of different types of piston in an HCCI engine: A review

Abstract: Homogenous charge compression ignition (HCCI) combines the advantages of spark ignition (SI) and compression ignition (CI) engines to improve fuel consumption and emission levels. HCCI engines have the advantage of relatively higher engine efficiency than SI engines while maintaining lower emissions levels than CI engines. Combustion in HCCI engines occurs spontaneously at any location once the fuel-air mixture reaches its chemical activation energy. Pistons have a major effect on controlling the combustion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…Bowl piston has the lowest average temperature while dome piston has the highest average temperature. This is due to the more efficient combustion and faster burning rate of air-fuel mixture on bowl piston compared to dome piston [14]. Faster burning rate means that the air-fuel mixture is burned completely in a shorter amount of time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowl piston has the lowest average temperature while dome piston has the highest average temperature. This is due to the more efficient combustion and faster burning rate of air-fuel mixture on bowl piston compared to dome piston [14]. Faster burning rate means that the air-fuel mixture is burned completely in a shorter amount of time.…”
Section: Resultsmentioning
confidence: 99%
“…After calculating the dimensions of the piston, the four types of piston head shapes are determined based on related studies. The four analyzed piston designs are flat-top piston, bowl piston, square bowl piston and dome piston since these piston designs are commonly used in the industries and they affect the combustion in cylinder differently which results in different deformation, temperature and stress distribution for different pistons [14]. All four piston designs are modelled using Solidworks based on the dimensions calculated.…”
Section: Radial Thickness Of Ringmentioning
confidence: 99%
“…However, due to the high mechanical strength, good thermal stability, high stability under vacuum, good anti-radiation, better solvent resistance, and wear resistance behaviour of polyimide (PI) and its composites under certain conditions, have made the tribological scientists worldwide to show more extensive concern on polyimide based materials because of its properties. 44,73 Over the decades, thermoplastic polyimide as one of the high performance engineering polymers have received considerable attention due to its extraordinary performance when used as a material in mechanical moving parts of a space systems. Song et al 74 observed that space exploitation and development, demand high performance polymer based matrix tribo-materials for weight reduction purpose, which could also serve in improving the reliability of mechanical moving parts.…”
Section: Overview Of Polyimide Matrix Materials For Thermal Mechanica...mentioning
confidence: 99%
“…To enhanced the performances of polyimide nanocomposites for engineering applications, the incorporation of nanofillers, such as inorganic oxides (SiO 2 , Al 2 O 3 , TiO 2 , ZnO 2 , ZrO 2 ), carbon nanotubes (CNTs), graphene (GN), graphene oxide (GO), boron nitride (BN), molybdenum disulfide (MoS 2 ), ionic liquids (ILs), carbon fibres (CF), aramid fibre (AF), glass fibre (GF), silicon nitride (Si 2 N 4 ), and carbon nitride (C 3 N 4 ) into the polyimide matrix has widely been explored. However, the current review focuses on the recent 44 advances on the thermal, mechanical, and tribological properties of polyimide reinforced nanocomposites for tribological system, as well as it processing, challenges and recommendation for future improvement.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the challenge of incontrollable combustion phasing, in other words, an unpredictable ignition timing [1]. This profound consequence of instability is mainly the result of the compression ignition applied to the Air-fuel mixture: the premixed ratio could significantly affect the chemical reaction rate, even leading to a circumstance of multiple combustion stages [2]. Traditionally, on the Otto cycle, the spark plug is used for the ignition process, providing a convenient and tractable way of combustion phasing.…”
Section: Introductionmentioning
confidence: 99%